2019
DOI: 10.1002/pbc.28129
|View full text |Cite
|
Sign up to set email alerts
|

The effect of graft‐versus‐host disease on outcomes after allogeneic stem cell transplantation for refractory lymphoblastic lymphoma in children and young adults

Abstract: Background Patients with relapsed or refractory lymphoblastic lymphoma (LBL) have a poor prognosis. The efficacy of allogeneic blood stem cell transplantation for treatment of this disease remains unclear in terms of transplantation‐related toxicity. Acute and chronic graft‐versus‐host diseases (GVHD) are both harmful to patients after allogeneic transplantation, but may have some positive effects through a substitute graft‐versus‐lymphoma effect. Methods To investigate the effect of GVHD on the survival of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, the roles of autologous HSCT and allogeneic HSCT in R/R-PTCL remain far more controversial. Although HSCT has certain beneficial effects, adverse events (AEs) will negatively influence survival as well . Therefore, this meta-analysis was performed to compare the efficacy and safety of autologous HSCT vs allogeneic HSCT in R/R-PTCL.…”
Section: Introductionmentioning
confidence: 99%
“…However, the roles of autologous HSCT and allogeneic HSCT in R/R-PTCL remain far more controversial. Although HSCT has certain beneficial effects, adverse events (AEs) will negatively influence survival as well . Therefore, this meta-analysis was performed to compare the efficacy and safety of autologous HSCT vs allogeneic HSCT in R/R-PTCL.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that graft‐versus‐lymphoma effect may partially overcome the poor prognostic significance of high‐risk features before HSCT. Similarly, several studies also reported that LBL/ALL patients, particularly those with relapsed/refractory disease, could benefit from graft‐versus‐lymphoma effect 56,57 …”
Section: Discussionmentioning
confidence: 94%
“…Similarly, several studies also reported that LBL/ALL patients, particularly those with relapsed/refractory disease, could benefit from graft-versus-lymphoma effect. 56,57 In the study of Levine et al 11 the 1-year and 2-year cumulative incidence of relapse was 32% and 34%, respectively, in LBL patients receiving matched sibling donor (MSD) allo-HSCT. In the present study, the 2-year cumulative incidence of disease progression was only 21%.…”
Section: Discussionmentioning
confidence: 99%
“…The NHL-BFM Study Group also reported that allo-HSCT is the only good prognostic factor for patients with relapsed LBL ( 26 ). The occurrence of aGVHD may be associated with better outcomes in patients with relapsed/refractory LBL who undergo allogeneic transplantation ( 27 ). Moreover, achieving CR1 before allo-HSCT is associated with a favorable OS, regardless of the disease subtype ( 28 ).…”
Section: Discussionmentioning
confidence: 99%